Differentially regulated miRNAs as prognostic biomarkers in the blood of primary CNS lymphoma patients. Issue 3 (February 2015) - Roth, Patrick; Keller, Andreas; Hoheisel, Jörg D.; Codo, Paula; Bauer, Andrea S.; Backes, Christina; Leidinger, Petra; Meese, Eckart; Thiel, Eckhard; Korfel, Agnieszka; Weller, Michael
Abstract Despite improved therapeutic regimens, primary CNS lymphoma (PCNSL) remains a therapeutic challenge. A prognostic classification of PCNSL patients may represent an important step towards optimised patient-adapted therapy. However, only higher age and low Karnofsky Performance Status (KPS) have repeatedly been reported to be associated with shorter overall survival (OS). Here we characterised microRNA (miRNA) fingerprints in the blood of PCNSL patients with short-term survival (STS) versus long-term survival (LTS) to assess their potential as novel prognostic biomarkers. Blood was collected from patients enrolled in the G-PCNSL-SG1 trial, a phase III study for patients with newly diagnosed PCNSL. miRNAs were extracted from the blood and analysed by next generation sequencing. The STS group comprised 20 patients with a median OS of 3 months and was compared to 20 LTS patients with a median OS of 55 months. The cohorts were balanced for age and KPS. Twelve annotated miRNAs were significantly deregulated between the two groups. Among them, miR-151a-5p and miR-151b exhibited the most prominent differences. Importantly, the combination of several miRNA allowed for a good separation between short- and long-term survivors with maximal Area Under Curve (AUC) above 0.75. Besides the known miRNAs we identified putative novel miRNA candidates with potential regulatory influence of PCNSL. Finally, the differential regulation of the most promising candidate miRNAs was confirmed by real-time polymerase chain reaction (PCR) in a validation cohort consisting of 20 STS and LTS patients. In conclusion, peripheral blood miRNA expression patterns hold promise as a prognostic tool in PCNSL patients.